Young Soccer Players With Higher Tactical Knowledge Display Lower Cognitive Effort. Issue 3 (June 2019) - Cardoso, Felippe da S. L.; González-Víllora, Sixto; Guilherme, José; Teoldo, Israel
The present study aimed to investigate whether the form and amount of declarative tactical knowledge (DTK) and procedural tactical knowledge (PTK) influence cognitive effort during soccer performance among young players. We assessed 36 male players from a Brazilian first-division soccer club; participants averaged 14.89 ( SD  = 1.42) years of age. We evaluated DTK from video simulation tests and PTK through the System of Tactical Assessment in Soccer. We assessed cognitive effort by measures of pupil diameter using Mobile Eye Tracking-XG while players viewed soccer video scenes and made game-related play decisions. After the assessment of tactical knowledge, we categorized the sample according to players' tactical knowledge into participants with higher and lower PTK and higher and lower DTK. Subsequently, we examined the both PTK and DTK groups on cognitive effort. Our results suggest that tactical knowledge influences cognitive effort in that players with higher PTK and DTK displayed less cognitive effort during soccer performance tasks. In conclusion, we observed that PTK and DTK influenced the cognitive effort younger soccer players expended while viewing soccer scenes and making soccer performance decisions.